Comparison of oligosaccharide labeling employing reductive amination and hydrazone formation chemistries - Krenkova, Jana; Dusa, Filip; Cmelik, Richard (Electrophoresis, 2020)
In this work, we compare labeling by two negatively charged fluorescent labels, 8-aminopyrene-1,3,6-trisulfonic acid (APTS) and 8-(2-hydrazino-2-oxoethoxy)pyrene-1,3,6-trisulfonic acid (Cascade Blue hydrazide [CBH]). Effectiveness of the labeling chemistries were investigated by 4-hydroxybenzaldehyde and maltoheptaose followed by LC/UV-MS and CE/LIF analysis, respectively. The reaction yield of APTS labeling was determined to be only ∼10%. This is due to reduction of almost 90% of the analyte by sodium cyanoborohydride to alcohol, which cannot be further labeled via reductive amination. However, the CBH labeling provides ∼90% reaction yield based on the LC/UV-MS measurements. The significantly higher labeling yield was also confirmed by CE/LIF measurements. Finally, the more effective hydrazone formation technique of CBH was characterized and applied for N-linked glycan analysis by CE/LIF.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Oligosaccharides; aminace; oligosacharidy; hydrazony; Pyrenes; Amination; Fluorescent Dyes; fluorescenční barviva; Electrophoresis, Capillary; pyreny; Chromatography, Liquid; chromatografie kapalinová; elektroforéza kapilární; Hydrazones